Numerical Simulation of MEMS Technology Integrated in a Small-Caliber Projectile - Dede Tarwidi (International Journal on Information and Communication Technology (IJoICT), 2016)
In this paper, numerical simulation of small-caliber projectile during external ballistic is presented. This work is aimed to find safe location to install microelectromechanical system (MEMS) inside a small-caliber projectile based on history and distribution of temperature. The MEMS technology is applied to increase performance of the projectile and it must be protected from damage due to high temperature during internal and external ballistic. Heat conduction equation in cylindrical domain is used to describe transient temperature of smallcaliber projectile. Finite element method with the appropriate boundary conditions is adopted to solve the heat conduction equation and to obtain temperature distribution inside projectile. Numerical results show that heat transfer behavior of the projectile at any point is greatly affected by the value of thermal conductivity of material while the external convection does not significantly affect to the heat distribution. The maximum temperatures obtained from temperature history are below threshold value of MEMS damage that is 71â„ƒ. The MEMS technology can be installed anywhere inside the projectile except at the rear surface of the projectile which experienced friction with the inner surface of gun barrel during internal ballistics.